The association of thyroid dysfunction with chronic plaque psoriasis: A hospital-based retrospective descriptive observational study - Ashwani Rana; Vikram K Mahajan; Pushpinder S Chauhan; Karaninder S Mehta; Satya Bhushan Sharma; Anuj Sharma; Reena Sharma (Wolters Kluwer Medknow Publications, 2020)
Background: Associations among thyroid dysfunction, thyroid autoimmunity, and clinical features including age, gender, disease duration, and severity of psoriasis is less studied. Objectives: To study frequency of thyroid dysfunction and thyroid autoimmunity and examine association among thyroid dysfunction, thyroid autoimmunity, and clinical features including gender, age, duration, and severity of psoriasis. Material and Methods: The medical records of 290 (m:f 2.15:1) patients aged 13-75 years with plaque psoriasis were analyzed for thyroid dysfunction and thyroid autoimmunity. Thyroid dysfunction was defined as 10% variation in any thyroid hormone levels. Thyroid autoimmunity was diagnosed from presence of antithyroid peroxide (anti-TPO) antibodies. Results: The majority, 57.9% patients, was aged ≥41 years (Type-2 psoriasis) and duration of disease was <5 years in 58.6% patients. Mild and moderate to severe psoriasis was present in 58.3% and 41.7% patients, respectively. Deranged thyroid functions were present in 29 (10%) patients. Hypothyroidism and hyperthyroidism occurred in 5.4% and 2.7% patients, respectively. Anti-TPO antibodies were observed in 13.5% patients; 11had hypothyroidism. There was no statistically significant difference in gender, age, duration, and severity of psoriasis when compared with patients having normal thyroid function tests. Conclusion: The study suggests possible thyroid dysregulation and thyroid autoimmunity in psoriasis but results need careful interpretation and clinical application. Their significance as standalone risk factor for the chronicity, severity, and relapses in psoriasis or whether thyroid hormone replacement or antithyroid drugs become a useful therapeutic option remains tenuous at best for need of more robust evidence. Retrospective, observational, cross-sectional study design, small number of patients, and lack of controls remain major limitations.